Long Noncoding RNA HCAL Facilitates the Growth and Metastasis of Hepatocellular Carcinoma by Acting as a ceRNA of LAPTM4B - Cheng-Rong Xie; Fei Wang; Sheng Zhang; Fu-Qiang Wang; Sen Zheng; Zhao Li; Jie Lv; He-Qiang Qi; Qin-Liang Fang; Xiao-Min Wang; Zhen-Yu Yin (Elsevier, 2017)
Long noncoding RNAs (lncRNAs) are a new class of regulatory noncoding RNAs. Emerging evidences indicate that lncRNAs play a critical role in the development of hepatocellular carcinoma (HCC). Although several lncRNAs have been annotated, the association of most lncRNAs with HCC is unknown. In this study, we investigated lncRNA alterations in HCC by performing lncRNA microarray analysis. We identified a novel lncRNA called HCC-associated lncRNA (HCAL) that was highly expressed in HCC tissues. HCAL upregulation was clinically associated with poor differentiation, intravascular cancer embolus, and decreased survival of patients with HCC. HCAL silencing significantly inhibited the growth and metastasis of HCC cells both in vitro and in vivo. Interestingly, transcriptome-sequencing analysis of HCAL-knockdown cells showed alterations in some cancer-related pathways. Mechanistically, HCAL directly interacted with and functioned as a sponge for microRNAs such as miR-15a, miR-196a, and miR-196b to modulate LAPTM4B expression. Taken together, our findings suggest the presence of a novel lncRNA-miRNA-mRNA regulatory network, i.e., the HCAL-miR-15a/miR-196a/miR-196b-LAPTM4B network, in HCC and indicate that HCAL may be a potential target for treating HCC.